Pyroptosis: shedding light on the mechanisms and links with cancers - You, Hong-mei; Wang, Ling; Meng, Hong-wu; Huang, Cheng; Fang, Guo-ying; Li, Jun (Frontiers in Immunology, 2023)
Pyroptosis, a novel form of programmed cell death (PCD) discovered after apoptosis and necrosis, is characterized by cell swelling, cytomembrane perforation and lysis, chromatin DNA fragmentation, and the release of intracellular proinflammatory contents, such as Interleukin (IL) 8, IL-1β, ATP, IL-1α, and high mobility group box 1 (HMGB1). Our understanding of pyroptosis has increased over time with an increase in research on the subject: gasdermin-mediated lytic PCD usually, but not always, requires cleavage by caspases. Moreover, new evidence suggests that pyroptosis induction in tumor cells results in a strong inflammatory response and significant cancer regression, which has stimulated great interest among scientists for its potential application in clinical cancer therapy. It's worth noting that the side effects of chemotherapy and radiotherapy can be triggered by pyroptosis. Thus, the intelligent use of pyroptosis, the double-edged sword for tumors, will enable us to understand the genesis and development of cancers and provide potential methods to develop novel anticancer drugs based on pyroptosis. Hence, in this review, we systematically summarize the molecular mechanisms of pyroptosis and provide the latest available evidence supporting the antitumor properties of pyroptosis, and provide a summary of the various antitumor medicines targeting pyroptosis signaling pathways.